Exploring the possibilities for stabilizing the sex ratio in India - Saurabh RamBihariLal Shrivastava; Prateek Saurabh Shrivastava; Jegadeesh Ramasamy (Turkish Journal of Public Health, 2015)
The sex ratio is an important demographic indicator for a nation. A wide range of adverse social consequences have been observed because of a skewed sex ratio in India. If India as a nation is to achieve the Millennium Development Goal – 3 (which promotes gender equality and ensures the empowerment of women), the primary target should be involve all those involved, so that a collective and comprehensive approach can be developed to counter the public health menace of an asymmetrical sex ratio. In conclusion, the nation’s program managers should prioritize the issue of a skewed sex ratio and work towards developing a coordinated response. Key Words: Sex ratio, policy makers, India.